Neurodevelopmental disorder risk in babies with history of hyperbilirubinemia - Baginda Hutahaean; Alifiani Hikmah Putranti; Kamilah Budhi Rahardjani (Indonesian Pediatric Society Publishing House, 2008)
Background Neurodevelopmental disorder (ND) is defined as failure to attain normal neurological function. Indirect bilirubin has essential role because its neurotoxic properties. Neonates with hyperbilirubinemia carry the risk to develop ND. Objective To determine the association between neonatal indirect hyperbilirubinemia and the risk of ND. Methods Neonates with indirect serum bilirubin (SIB) level >10 mg/dL, admitted in the period of October 2004-August 2005, were included in this study. They were followed-up and screened using Bayley Infant Neurodevelopmental Screener (BINS) at three, six and nine months. Mann-Whitney test was used to test the hypothesis. Results Forty-eight neonates were included in the study. Mean SIB level of subjects with ND risk was 20.5 mg/dL (SD=6.06; p<0.001). Mean SIB level of subjects who developed ND at three, six and nine months was 31.6 mg/dL (SD=4.02), 18.4 mg/dL (SD=2.92) and 18.4 mg/dL (SD=5.41), respectively. There was statistically significant correlation between SIB level and ND risk (R=+0.64; P<0.001). There was also statistically significant correlation between SIB level and the onset of ND (R=-0.63; P< 0.001). Conclusion There is a correlation between neonatal SIB level and the risk of ND in babies.